THE INFLUENCE OF INFORMATION SERVICES TO IMPROVE THE EMOTIONAL INTELLIGENCE OF CLASS X STUDENTS AT TAMANSISWA VOCATIONAL SCHOOL MEDAN - Siddiq Habibullah, Muhammad; Muharni, Tetty (Faculty of Tarbiyah nad Teacher Training, 2023)
This research aims to determine the effect of Information Services to Increase the Emotional Intelligence of Class X Students at SMK Tamansiswa Medan for the 2023/2024 Academic Year.